Analysis of the Competitive Activity Structure of Skilled Female Basketball Players - Eduard Doroshenko; Ruslana Sushko; Valerij Shamardin; Volodymyr Prykhodko; Iryna Shapovalova; Daria Yelisieieva; Oksana Demidova; Artem Yakovenko (Physical Education Theory and Methodology, 2020)
The study purpose was to examine, analyze, and generalize the competitive activity structure based on the hierarchy of technical and tactical indicators of skilled female basketball players in won and lost games using principal component analysis.